2017
DOI: 10.1038/s41598-017-16658-x
|View full text |Cite
|
Sign up to set email alerts
|

Young onset type 2 diabetic patients might be more sensitive to metformin compared to late onset type 2 diabetic patients

Abstract: It is unknown whether YOD (young onset diabetes) and LOD (late onset diabetes) require similar insulin doses for intensive insulin therapy with a metformin add-on to achieve glycemic control. We analyzed data from our two previously performed randomized, controlled open-label trials. Patients were randomized to receive either continuous subcutaneous insulin infusion (CSII) therapy or CSII combined with metformin therapy for 4 weeks. The studies concentrated on the differences in the insulin doses used for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Then, recruited subjects received 7-day CSII therapy to achieve glycemic control. CSII therapy was provided with aspart (Novo Nordisk, Bagsvaerd, Denmark) using a Medtronic insulin pump (Northridge, CA) as previously described [ 6 , 18 , 20 ]. After subjects achieved glycemic control, defined as a fasting and 2-h post prandial capillary blood glucose concentration between 6.1 and 8.0 mmol/l [ 21 ], patients were randomized 1:1 to two groups receiving: (1) 4 days of Novo Mix 30 (Novo Nordisk, Bagsværd, Denmark) followed by 2 days of Humalog Mix 50 (humalog ® Mix50™, Eli Lilly and Co., Indianapolis, IN, USA); (2) 4 days of Humalog Mix 50 followed by 2 days of Novo Mix 30.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, recruited subjects received 7-day CSII therapy to achieve glycemic control. CSII therapy was provided with aspart (Novo Nordisk, Bagsvaerd, Denmark) using a Medtronic insulin pump (Northridge, CA) as previously described [ 6 , 18 , 20 ]. After subjects achieved glycemic control, defined as a fasting and 2-h post prandial capillary blood glucose concentration between 6.1 and 8.0 mmol/l [ 21 ], patients were randomized 1:1 to two groups receiving: (1) 4 days of Novo Mix 30 (Novo Nordisk, Bagsværd, Denmark) followed by 2 days of Humalog Mix 50 (humalog ® Mix50™, Eli Lilly and Co., Indianapolis, IN, USA); (2) 4 days of Humalog Mix 50 followed by 2 days of Novo Mix 30.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly 20% of patients using insulin pump therapy and one-fifth of patients had symptomless nocturnal hypoglycemia [ 15 ]. Studies further highlighted that older patients had high incidences of hypoglycemia [ 16 , 17 ], although we observed that newly diagnosed male and female T2D patients required similar insulin doses to maintain glycemic control [ 18 ]. The gender differences in insulin doses required to maintain euglycemic control in patients with longstanding T2D remain largely unknown.…”
Section: Introductionmentioning
confidence: 97%
“…The recruited subjects received CSII therapy from day 2 to day 9, as previously described [12,15,16]. Then, patients were randomly assigned 1 : 1 to 2 groups receiving (1) 4 days of Novo Mix 30 thrice daily (Novo Nordisk, Bagsvaerd, Denmark) followed by 2 days of Humalog Mix 50 thrice daily (Humalog® Mix 50™, Eli Lilly and Company, IN, USA); (2) 4 days of Humalog Mix 50 thrice daily followed by 2 days of Novo Mix 30 thrice daily.…”
Section: Methodsmentioning
confidence: 99%
“…We hence hypothesized that male and female patients may have different responses to midor low-premixed insulin analogues with regard to glycemic variations in patients with T2D. We used continuous glucose monitoring (CGM) to monitor glucose profile as CGM provides rigorous 24 h glucose profiles [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the GOLD [ 25 ] and DIAMOND [ 26 ] trials showed that among patients with type 1 DM treated with multiple daily insulin injections, the use of CGM resulted in better glycemic control than did conventional treatment. Moreover, several studies have shown that the use of CGM can improve the mean amplitude of glycemic excursion (MAGE) and result in better glycemic control in persons with type 2 DM [ 27 30 ]. A recent meta-analysis of randomized controlled trials conducted on the utility of real-time and retrospective CGM in patients with type 2 DM showed that CGM in these patients could reduce HbA1c levels and time spent with hypoglycemia [ 31 ].…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%